Technology, International Trade, and Pollution from US Manufacturing - Levinson, Arik (American Economic Review, 2009)
Pollution emitted by US manufacturers declined markedly over the past several decades, even as real manufacturing output increased. I first show that most of the decline in US manufacturing pollution has resulted from changing production processes (“technology”), rather than changes in the mix of goods produced. I then show that increased net imports of polluting goods (“international trade”) accounts for only a small portion of the pollution reductions from the changing mix of goods. Together, these two findings demonstrate that shifting polluting industries overseas explains only a minor part—less than 10 percent—of the cleanup of US manufacturing. (JEL F18, L23, L60, O30, Q52, Q53)